An Analysis of the Factors Affecting Income Distribution Inequality in Regencies/Municipalities in Bali Province - Putu Indah Cahyani Pradina; Sudarsana Arka (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Income distribution inequality is a key indicator in evaluating the success of a region’s economic development. This study aims to analyze the influence of several factors on income distribution inequality across regencies/municipalities in Bali Province. The independent variables examined include economic growth, the regency/municipal minimum wage (UMK), education level, and locally generated revenue (PAD). The research method employed is panel data regression analysis using secondary data obtained from the Central Bureau of Statistics (BPS). The objectives of this study are: (1) to analyze the simultaneous effects of economic growth, UMK, education level, and PAD on income distribution inequality in regencies/municipalities in Bali Province, and (2) to analyze the partial effects of these variables on the same outcome. The study uses secondary data with a total of 90 observation points.